Genome‐wide study of the human lipidome and links to Alzheimer's disease risk: Genome‐metabolome‐phenome: Towards an integrated molecular atlas for Alzheimer's disease. (7th December 2020) - Meikle, Peter J.; Giles, Corey; Cadby, Gemma; Huynh, Kevin; Mellett, Natalie A.; Olshansky, Gavriel; Smith, Alexander; Nguyen, Anh; Chatterjee, Pratishtha; Martins, Ian; Laws, Simon M.; Bush, Ashley I.; et al.
Abstract: Background: Dysregulation of lipid metabolism is as an important – and modifiable – risk factor for the initiation and progression of Alzheimer's disease (AD). Although lipid metabolism is established as crucial to numerous biological processes, the genetic factors that influence inter‐individual variation are still not well understood. To address this issue, we apply an integrative approach to link genetic variants with altered lipid metabolism and AD. Method: Lipidomic profiling was performed using liquid chromatography coupled electrospray‐ionization tandem‐mass spectrometry on 4, 492 genotyped individuals from the Busselton Family Health Study. We performed genome‐wide association analysis of 596 lipid species and 33 lipid classes using linear‐mixed models, correcting for age, sex, their interactions, 10 genomic principal components and an empirical genetic relatedness matrix. To account for lipoprotein mediated associations, the analysis was repeated with HDL‐C, triglycerides and total cholesterol as covariates. Additionally, collider bias was avoided by conditioning using multi‐trait‐based conditional and joint analysis. Validation of genome‐wide significant associations is supported by replication in the Australian Imaging, Biomarker & Lifestyle Study of Ageing (n = 1, 112) and Alzheimer's Disease Neuroimaging Initiative (n = 757) cohorts. Result: Over 70, 000 genome‐wide significant (p<5e‐08) associations were identified, with 451 lipid species having at least one significant association. Approximately 70% of the observed associations are independent of lipoprotein measures. We observed associations (p<1.0E‐6) between lipid species and seven loci containing genes previously identified as risk factors for AD, including ApoE, ABCA7 and SLC24A4. We further identify 1252 variants (92 independent gene regions) that associated (p<5.0E‐8) with the 71 lipid species we identified as significantly associated with incident AD in a combined meta‐analysis of the AIBL and ADNI cohorts. Conclusion: By linking lipid species to AD, through genetic associations, we highlight potential therapeutic targets for monitoring, prevention and treatment.